Role Model Implementasi Kurikulum Merdeka Belajar Kampus Merdeka Pada Program Studi Non-Agama - Rizqon Halal Syah Aji; Muhammad Hartana Iswandi Putra (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
Higher education in Indonesia presents a complex problem. The influence of the digitalization era and also the impact of the pandemic caused the world of Indonesian education to experience significant changes. The application of the concept of the Merdeka Learning Campus Merdeka (MBKM) curriculum concept is an effort to answer problems in the higher education environment, including the UIN Syarif Hidayatullah Jakarta. This study aims to determine the effectiveness of the implementation of the MBKM curriculum. To step up the objectivity of the research, a survey method was used on 135 student respondents from non-religious study programs, with the respondent's criteria being at least in the fifth semester of lectures. From the survey results, it was found that students tend to want to do apprenticeship programs and choose to implement them in companies, both international, national and e-commerce. Then the students were seen to be interested in doing entrepreneurial activities and undergoing student exchanges to other campuses. From the results of this survey, it is hoped that actions can be taken to implement activities in the semester that are deemed appropriate to the teaching and learning processes that exist in the campus environment. So that this will have an impact on the effectiveness and efficiency of the implementation of the MBKM program.Keywords: Learning Process; Curriculum; Free to Learn; Independent Campus AbstrakPendidikan tinggi di Indonesia menyajikan masalah yang kompleks. Pengaruh era digitalisasi dan juga dampak pandemi menyebabkan dunia pendidikan Indonesia mengalami perubahan secara signifikan. Penerapan konsep kurikulum Merdeka Belajar Kampus Merdeka (MBKM) adalah upaya menjawab persoalan di lingkungan perguruan tinggi tidak kecuali pada lingkungan UIN Syarif Hidayatullah Jakarta. Penelitian ini bertujuan untuk mengetahui efektifitas penerapan kurikulum MBKM. Untuk melangkah objektifitas penelitian yang dituju, maka digunakan metode survei terhadap 135 responden mahasiswa yang berasal dari program studi non agama, dengan kriteria responden adalah minimal berada di semester kelima perkuliahan. Dari hasil survei yang didapat bahwa mahasiswa cenderung ingin melakukan program pemagangan dan memilih melaksanakannya di perusahaan, baik internasional, nasional maupun e-commerce. Kemudian mahasiswa terlihat akan ketertarikannya melakukan aktivitas kewirausahaan dan menjalani pertukaran pelajar ke kampus lain. Dari hasil survei ini diharapkan dapat diambil tindakan pelaksanaan kegiatan di semester yang dirasa sesuai dengan proses pengajaran dan pembelajaran yang ada dilingkungan kampus. Sehingga hal ini akan berdampak pada keefektifitasan dan efisiensi pelaksanaan program MBKM.Kata Kunci: Proses Pembelajaran; Kurikulum; Merdeka Belajar; Kampus Merdeka